Memikirkan Kembali Strategi Mengajar Dosen: Analisis Terhadap mahasiswa Pendiam Pada Diskusi Kelas di IAIN Syaikh Abdurrahman Siddik, 2016 - Noblana Adib (Sustainable, 2020)
The silent students in the class discussions. What is the cause, is it because they are not confident in front of their classmates or their lecturers? How do they see lecturers, as people, who will help them learn, or as people who will embarrass them in the lecture? What should be the right learning strategy, how lecturers should help students to be active in class. Meanwhile, the students are not elementary school students, but the adults who study in the college. They should be more courageous in expressing their opinions in various class discussions. This study argues the more harmonious the relationship between lecturers and students is, the more successful students are in completing their studies, and the more professional the lecturers are.